Emergence/Subsidence Histories Along the Carnegie and Cocos Ridges and Their Bearing Upon Biological Speciation in the Galápagos. (5th November 2018) - Orellana‐Rovirosa, Felipe; Richards, Mark
Abstract: Using plate motion reconstructions for the Nazca, Cocos, and South American plates in relation to the Galápagos hotspot, we find that age‐depth dependence of bathymetry, Galápagos plume dynamic topography, crustal relaxation, and magmatic production permit reasonable estimates for the subsidence of former islands along the Carnegie and Cocos Ridges. Our dynamic topography estimates are partially based upon geodynamic theory (fluid mechanics and elasticity) and also upon detailed bathymetric observations and analysis. For three different target areas over Carnegie Ridge and two over Cocos Ridge, we infer subaerial landmasses over the past 20 Ma. We provide rough estimates of the surface areas of these paleo‐archipelagos, which were comparable to that of the present‐day Galápagos archipelago. We construct a history of emerged (paleo‐island) topography along the conjugate pair Carnegie‐Cocos hotspot tracks and infer that significant subaerial landscapes existed for at least the past 20 Ma. The genetic ancestors of endemic faunal species in Galápagos (e.g., marine iguanas) migrated away from South America, genetically diverging from their land counterparts much earlier than the age of the present Galápagos Islands ( 3 Ma). At 16.5 Ma, the total emerged landmass on the Carnegie Ridge alone may have been 2.5 times that of the current Galápagos archipelago. (The conjugate landmass along the Cocos Ridge has been subducted.) We propose that this large landmass, at least one‐fourth the size of Iceland, be called Darwinia in recognition of its importance in the evolution of some Galápagos endemic flora and fauna made famous by Darwin's explorations. Plain Language Summary: Using reconstructed motions of the Nazca, Cocos, and South American tectonic plates with respect to the upwelling Galápagos mantle plume (hotspot), we studied the regional mechanical and thermal evolution of the crust and lithosphere. Using the theory of viscous fluids, elastic solids, and thermodynamics, and considering diverse observations of the present‐day seamounts and elevated Carnegie and Cocos ridges (Galápagos hotspot tracks), we modeled the vertical displacements of the seafloor through time in the region. With this framework, we found that portions of these seafloor between western South America and the Galápagos archipelago ( 1, 000 km off‐shore) were so much shallower in the past and that they were above sea level, as emerged lands or islands: during the past 20 million years, different portions of the seafloor Carnegie and Cocos Ridges exhibited important archipelagos. This is crucial considering that ancient species of lizards, iguanas, snails, snakes, and birds in South America might have migrated westward, offshore, moving over the available emerged lands (archipelagos), for millions of years, evolving in response to the changing natural environment. Finally, their descendants arrived to the westernmost emerged land (the ancient archipelagos have gradually submerged and subsided) of the region, which is actually the pristine Galápagos archipelago. This work can be helpful for future evolutionary biology studies. Key Points: Motions and tectonics of Nazca, Cocos and SouthAmerican plates are considered with respect to the Galápagos hotspot Thermo‐mechanical assessments of dynamic topography are carried out to estimate paleo‐elevations associated with the Galápagos mantle plume Emerged lands on paleo‐archipelagos likely determined biological speciation in the region